Multi-agent communication - Swe, Phone Myat. (2009)
The purpose of this report is to document the learning process and findings in the implementation of Agent Communication Language (ACL) for multi-agent systems using FIPA ACL Specifications and to share the knowledge gained from the development of the communication prototype. Agents need to interact with each other in a multi-agent system to solve common problems and to achieve individual or shared goals, which are beyond the capabilities of individual agents and a collaboration between agents is required. In order to effectively collaborate and interact, agents need a common language to share or exchange information, to engage in negotiations and to make coordinations among agents, which leads to the need of Agent Communication Language (ACL). FIPA ACL Specifications has standardized 22 Communicative Acts, and four Interaction Protocols. Communicative acts are different type of messages utilized in various conditions during communication. Interaction Protocols define the flow of communication such as when an agent receives certain message, what options are available for the receiving agent to reply.